Exploring user experience in game using heart rate device - Nazlena Mohamad Ali; Siti Zahidah Abdullah; Juhana Salim; Riza Sulaiman; Azlina Ahmad; Halimah Badioze Zaman; Hyowon, Lee (Penerbit Universiti Kebangsaan Malaysia, 2012)
In this paper we describe our experience using psycho physiological techniques to explore user experience in playing games. We used heart rate devices to measure the user experience during a simulation game play called The Sims™ 3. This study does not emphasize the measurement of data, but focuses mainly on experiences in applying a psycho physiological method to capture user experience while playing games. We measured selected participants’ heart rates using a heart rate detector while playing a game. The majority of participants had an average of 60-90 bmp heart rates (HR). Our analysis revealed that there was no difference in HR between novice and non-novice players, but that HR had mostly similar patterns amongst the players throughout the game-playing experiment. HR was higher during the interesting or fun activities or tasks. We end by discussing lessons learnt and issues identified in the experiment which are useful for future enhancement.